LAPORAN KEUANGAN MASJID: PERSPEKTIF AKUNTANSI SYARIAH DAN PENCEGAHAN FRAUD - Wahyu Ansahrizal (Journal of Sharia Economics, 2023)
This study aims to qualitatively analyze and find out the financial reports presented by mosques based on the perspective of Sharia accounting and fraud prevention. This study used a descriptive qualitative method. The data used in this research is secondary data. Secondary data was obtained from the mosque's financial reports. The results of this study indicate that DSAK IAI (Financial Accounting Standards Board of the Indonesian Institute of Accountants) as a professional organization of accountants in Indonesia issued ISAK 35 to strengthen aspects of recognition, measurement, presentation and disclosure so that the financial statements of mosques presented based on ISAK 35 include statements of financial position, comprehensive income statements, cash flow statements, reports on changes in net assets, and notes on financial statements in order to create financial reports that are easy to understand, have relevance and have high comparability to strengthen aspects of accountability and transparency in order to minimize the occurrence of fraudulent practices.